2000
DOI: 10.1007/pl00013791
|View full text |Cite
|
Sign up to set email alerts
|

Microwaves emitted by cellular telephones affect human slow brain potentials

Abstract: The influence of electromagnetic fields (EMF) emitted by cellular telephones on preparatory slow brain potentials (SP) was studied in two experiments, about 6 months apart. In the first experiment, a significant decrease of SP was found during exposure to EMF in a complex visual monitoring task (VMT). This effect was replicated in the second experiment. In addition to the VMT, EMF effects on SP were analysed in two further, less demanding tasks: in a simple finger movement task to elicit a Bereitschaftspotenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 34 publications
1
47
0
3
Order By: Relevance
“…Freude et al [1998] found that a 916.2 MHz EMF pulsed at 217 Hz resulted in signi®cant decreases in brain slow potentials, most pronounced in the right hemisphere central and temporal-parietal-occipital areas, but not frontal regions. A further study by Freude et al [2000] using the same exposure conditions con®rmed results of their previous experiment, ®nding decreased event related slow potentials at central and parieto-temporooccipital regions, but not at the frontal regions and without decrement in performance task measures. Krause et al [2000a] found that a 902 MHz EMF pulsed at 217 Hz increased the relative EEG power in the 8±10 Hz (alpha) range, a task speci®c ®eld effect on the retrieval portion of a working memory task.…”
supporting
confidence: 72%
“…Freude et al [1998] found that a 916.2 MHz EMF pulsed at 217 Hz resulted in signi®cant decreases in brain slow potentials, most pronounced in the right hemisphere central and temporal-parietal-occipital areas, but not frontal regions. A further study by Freude et al [2000] using the same exposure conditions con®rmed results of their previous experiment, ®nding decreased event related slow potentials at central and parieto-temporooccipital regions, but not at the frontal regions and without decrement in performance task measures. Krause et al [2000a] found that a 902 MHz EMF pulsed at 217 Hz increased the relative EEG power in the 8±10 Hz (alpha) range, a task speci®c ®eld effect on the retrieval portion of a working memory task.…”
supporting
confidence: 72%
“…Eulitz et al reported a modulation in the high-frequency bands of the EEG after task-relevant but not after standard auditory stimuli [26]. Freude et al found an effect on preparatory slow brain potentials for visual monitoring tasks, but not for less demanding tasks such as finger movements [31,32]. Krause et al reported event-related changes of the desynchonisation/synchonisation responses in the EEG for auditory and visual memory tasks [61,62].…”
Section: Changes In Eeg-and Sleep-parametersmentioning
confidence: 99%
“…This influence is practically unknown, although it is generally recognized that such EMFs affect the central nervous system. It has already been demonstrated that EMFs may affect EEG recordings in subjects performing complex mental tasks [8,9], as well as modify human working memory and cognitive functions [10,11]. Thus, it seems reasonable to suppose that an EMF emitted by a mobile phone while driving a motor vehicle may adversely affect a driver's response to road traffic situations.…”
Section: Introductionmentioning
confidence: 99%